Modified grid method for solving linear differential equation equipped with variable coefficients based on Taylor series - A. A. Usov; V. P. Radchenko (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2008)
The modified grid method for solving value boundary problems for the linear differential equations based on Taylor development is described. It was demonstrated that the accuracy of the proposed method is much greater than that of a classical grids method. The results of numerical experiments are quoted.